Migrants and Masculinity in High-Rise Nairobi The Pressure of being a Man in an African City - Schmidt, Mario (Making & Remaking the African City: Studies in Urban Africa, 2024)
Pipeline is a low-income, high-rise-tenement settlement in Nairobi's marginalized East and one of sub-Saharan Africa's most densely populated estates. An aspirational place where fleeting forms of capitalist consumption reassure migrants of an upward trajectory, it is also a place where their ambitions of long-term economic success and stable romantic relationships are routinely thwarted. This book explores how men who migrate to Nairobi from Western Kenya navigate this tension that is generated by the contrast between their view of Pipeline as a launching pad for their personal and professional careers and the fact that they face constant economic, romantic, and personal backlashes. Drawing on over two years of fieldwork, the book reveals that many male migrants design their future on trajectories of personal and economic growth but have to adjust or indefinitely postpone their plans once they arrive in Kenya's capital. Under the pressure to succeed from romantic partners, spouses, rural kin, and children, they create and participate in homosocial spaces where a sense of brotherhood emerges and their experience of pressure is attenuated. Alongside a deep ethnographic exploration of how male migrants model their financial, physical, and mental well-being in three different masculine spaces - an ethnically homogenous investment group, an interethnic gym, and the semi-digital sphere of self-help books, workshops, and motivational trainings on man- and fatherhood - this book brings a new perspective to our understanding of urban African life and the nature of masculinity. This title is available under the Creative Commons license CC BY-NC-ND, with funding from the Max Planck Institute for Social Anthropology Open Access Fund and the German Research Foundation.